Psychosocial status and quality of life of adolescent girls in Karnataka, India - Rajachar, Veena; Gupta, Manoj Kumar (International Journal of Research in Medical Sciences, 2017)
Background: This study was conducted with the objective to assess the psychosocial status and quality of life (QOL) of adolescent girls in Karnataka, India. Methods: This was a cross sectional community based study which was conducted on 400 adolescent girls each in rural (Bellary district) and urban (Bangalore district) areas of Karnataka, India. WHO’s ‘HEEADSSS’ questionnaire and ‘WHOQOL-BREF’ tool have been used to assess psychosocial status and quality of life of adolescent girls, respectively. Results: It was observed that nearly 5% girls were at severe and very severe risk of developing psychosocial abnormalities in both rural and urban study area. The mean QOL score was highest for social relations (7102±21.6) and was minimum for physical domain (49.59±12.63). Conclusions: This calls for urgent community based interventions directed to adolescents and their families having higher vulnerability for psychosocial abnormalities and poor quality of life.